(untitled) (Journal of the College of Education for Women, 2019)
This study is concerned look at the role of satellite channels in the dissemination ofconsumer culture that has become part of our everyday lives , which is a dangerousphenomenon on society , so the study is aimed at introducing the concept of consumer cultureand the risks to individuals , which conducted a field study on a sample of students from theUniversity of Baghdad, as they represent an important category of the society they are a classof young people to get to know the impact of satellite television on them through their variousprograms and serials, films and ads may develop consumer culture they have , including inrespect of ideas and information , where the questionnaire was developed to ensure differentquestions and distributed to the research sample , and results show that the Spread a largeproportion of the sample are affected , including its programs and informational materialswhich affects the consumption of goods and culture.